Role of ERCP in Obstructive Jaundice - Javed Iqbal, Makil Shah, Mansour Ullah, Zia Ul Islam, Muhammad Jafar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the diagnostic role of ERCP in the management of obstructive jaundice. Materials and Methods: This cross-sectional study was done in Lady Reading Hospital Peshawar. In this study 60 patients with obstructive Jaundice were enrolled from April 2022–September 2022. All the enrolled patients were undergoing ERCP. Results: Total 80 patients were enrolled with mean age of 47.08±12.1 years. Out of total patients 68.3% were male and 31.7% were female. Stenting was done in 43.3% of patients and success rate was 88.5% and failure rate was 11.5%. Stone extractions were done in 20% of patients and success rate was 75.0%. Warm extractions were done in 10% and success rate was 100.0%. Sphincterotomy was done in 13.3% of patients and success rate was 100%. Some post complications were found, and the most common complication was acute pancreatitis that was 6.7%, followed by perforation that was 5%. Other post procedure complication were bleeding and acute cholangitis. Practical implication: In our study we find out that ERCP is an important diagnostic and therapeutic modality for evaluation of patients with obstructive jaundice. In our study the success rate is acceptable for ERCP in the management of obstructive jaundice. So this study will help the health practioner to choose better treatment option inorder to treat Obstructive Jaundice. Despite of its associated complication, ERCP is a reliable method in treating obstructive jaundice. Conclusion: It is concluded that ERCP is a best procedure having an affective role in the management of obstructive jaundice despite of complication. The success rate is in acceptable domain for ERCP in the management of obstructive jaundice. Keywords: Endoscopic retrograde cholangiopancreatography, Obstructive jaundice, Acute pancreatitis, Complication